Pengaruh Kualitas Pelayanan Kesehatan dan Kepercayaan Terhadap Kepuasan Pasien: Studi Kasus Pada Pasien UPTD Puskesmas Sadananya - Faridah Siti Luthfiana; Enas Enas; Ferey Herman (Universitas 45 Surabaya, 2024)
This research aims to find out how patient satisfaction is influenced by service quality and trust. This research used a sample of 100 respondents. The sampling strategy utilized an unintentional sampling approach. Questionnaires were used in data collection. Using multiple linear regression analysis, F test, coefficient of determination, t test, validity and reliability tests, as well as other quantitative analytical techniques are used to analyze the data. Based on the t test, the relationship between patient satisfaction and the quality of health services partially produces a value of 7.968, while the relationship between patient satisfaction and trust produces a value of 5.350. Based on the F test results of 128.788, this means that the quality of health services and trust simultaneously influence patient satisfaction. This research found that patient satisfaction at UPTD Puskesmas Sadananya was influenced positively and significantly by service quality and trust, both partially and simultaneously. Recommendations for this research include, among others, that the UPTD director of the Sadananya Community Health Center carry out routine assessments to uphold services and warn medical personnel to provide a friendly and kind attitude.